SPACE WEATHER AND A STATE OF CARDIOVASCULAR SYSTEM OF HUMAN BEING WITH A WEAKENED ADAPTATION SYSTEM - Samsonov, S. N. (Одеські астрономічні публікації, 2013)
As has been shown in [Samsonov et al., 2013] even at the considerable disturbances of space weather parameters a healthy human being did not undergo painful symptoms although measurements of objective physiological indices showed their changes. At the same time the state of health of people with the weakened adaptation system under the same conditions can considerably be deteriorated up to fatal outcome. The analysis of results of the project “Heliomed” and the number of calls for the emergency medical care (EMC) aroundYakutskas to cardiovascular diseases (CVD) has shown: - the total number of calls for EMC concerning myocardial infarction (MI) per year near the geomagnetic disturbance maximum (1992) exceeds the number of calls per year near the geomagnetic activity minimum (1998) by a factor of 1,5 and concerning to strokes - by a factor of 1,8. - maxima of MI are observed during spring and autumn periods coinciding with maxima of geophysical disturbance; - the coincidence of 30-32 daily periods in a power spectrum of MI with the same periods in power spectra of space weather parameters (speeds and density of the solar wind, interplanetary magnetic field, geophysical disturbance); - the existence of 3 maxima of the number of calls for EMC: a) at the moment of disturbance on the Sun; during a geophysical disturbance (in 2-4 days after a disturbance on the Sun); in 2-4 days after a geophysical disturbance; - the availability of coincidence of insignificant disturbances of space weather parameters with changes of the functional state of cardiovascular system of a human being with the weakened adaptation system and the occurrence of MI and strokes at considerable values of such disturbances is explained by a quasi-logarithmic dependence of the response of human being organisms to the environment disturbance intensity.